Persepsi Dan Pengalaman Komite Keperawatan Dalam Penilaian Kinerja Perawat Manajer di Rumah Sakit - Umi Eliawati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
This study aims to explore the perceptions and experiences of the nursing committee in assessing the performance of nurse managers, particularly unit heads, in hospitals. Using a descriptive interpretive qualitative approach, data were collected through Focus Group Discussions (FGDs) involving seven participants from five hospitals in Pekanbaru and its surroundings. Thematic analysis revealed four main themes: the committee’s understanding of performance appraisal, encountered barriers and challenges, expectations for improvement, and the perceived impact of the appraisal on motivation, career development, and service quality. The study recommends the implementation of a more continuous, transparent, and career-integrated performance evaluation system that supports nursing service quality enhancement.